Aminoacyl tRNA synthetases as potential drug targets of the Panthera pathogen Babesia - Chhibber-Goel, Jyoti (Parasit Vectors, 2019)
BACKGROUND: A century ago, pantheras were abundant across Asia. Illegal hunting and trading along with loss of habitat have resulted in the designation of Panthera as a genus of endangered species. In addition to the onslaught from humans, pantheras are also susceptible to outbreaks of several infectious diseases, including babesiosis. The latter is a hemoprotozoan disease whose causative agents are the eukaryotic parasites of the apicomplexan genus Babesia. Babesiosis affects a varied range of animals including humans (Homo sapiens), bovines (e.g. Bos taurus), pantheras (e.g. Panthera tigris, P. leo, P. pardus) and equines. Babesia spp. are transmitted by the tick vector Ixodes scapularis or ticks of domestic animals, namely Rhipicephalus (Boophilus) microplus and R. (B.) decoloratus. At the level of protein translation within these organisms, the conserved aminoacyl tRNA synthetase (aaRS) family offers an opportunity to identify the sequence and structural differences in the host (Panthera) and parasites (Babesia spp.) in order to exploit these for drug targeting Babesia spp. METHODS: Using computational tools we investigated the genomes of Babesia spp. and Panthera tigris so as to annotate their aaRSs. The sequences were analysed and their subcellular localizations were predicted using Target P1.1, SignalP 3.0, TMHMM v.2.0 and Deeploc 1.0 web servers. Structure-based analysis of the aaRSs from P. tigris and its protozoan pathogens Babesia spp. was performed using Phyre2 and chimera. RESULTS: We identified 33 (B. bovis), 34 (B. microti), 33 (B. bigemina) and 33 (P. tigris) aaRSs in these respective organisms. Poor sequence identity (~ 20–50%) between aaRSs from Babesia spp. and P. tigris was observed and this merits future experiments to validate new drug targets against Babesia spp. CONCLUSIONS: Overall this work provides a foundation for experimental investigation of druggable aaRSs from Babesia sp. in an effort to control Babesiosis in Panthera.